1999
DOI: 10.1111/j.1445-5994.1999.tb01586.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial risk estimation in systemic sclerosis

Abstract: This study substantially increases the otherwise small list of documented instances of familial systemic sclerosis. More importantly, it quantifies the risk for the first time, ranking it as the disease's most powerful determinant identified to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 19 publications
7
35
0
1
Order By: Relevance
“…Our group (4) reported 11 cases of familial SSc in a US cohort of 703 cases, for a prevalence of 1.6%. This was remarkably similar to results of an earlier study by Englert et al (5), who found 10 cases of SSc in firstdegree relatives of 710 SSc probands in an Australian cohort, for a prevalence of 1.4%. A positive family history of SSc, although infrequent, remains the strongest risk factor for SSc yet identified, given its low population prevalence (0.026%) (4).…”
supporting
confidence: 81%
“…Our group (4) reported 11 cases of familial SSc in a US cohort of 703 cases, for a prevalence of 1.6%. This was remarkably similar to results of an earlier study by Englert et al (5), who found 10 cases of SSc in firstdegree relatives of 710 SSc probands in an Australian cohort, for a prevalence of 1.4%. A positive family history of SSc, although infrequent, remains the strongest risk factor for SSc yet identified, given its low population prevalence (0.026%) (4).…”
supporting
confidence: 81%
“…Studies of SSc in families and twins are particularly important in determining the relative role of genetic and environmental factors in the development of SSc. Familial SSc studies have shown an absolute risk of 1.0-1.7% in first-degree relatives [33,34], suggesting a genetic contribution to disease pathogenesis. In our studies of twins with SSc, we found a low concordance (4.7%) for SSc, but a high concordance for the presence of antinuclear antibodies (> 90%) and shared gene expression profiles of dermal fibroblasts from monozygotic twins [35••, 36].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Evidence suggesting that genetic factors contribute to the disease includes the familial clustering of SSc, the high frequency of other autoimmune disorders in relatives of affected patients, and the reported effect of ethnicity on the clinical presentation and outcome of the disease [65,73,74]. In addition, environmental agents (such as viruses, drugs, chemicals etc.)…”
Section: Systemic Sclerosis (Ssc)mentioning
confidence: 97%